Bibliometric analysis of acute limb ischemia research: Global trends and key insights from 2000-2024 - Abiseka Panji Baskoro; Enrico Ananda Budiono; Heru Sulastomo; An Aldia Asrial (Heart Science Journal, 2026)
Background: Acute Limb Ischemia (ALI) remains a critical vascular emergency, necessitating understanding to prevent devastating outcomes. Despite its clinical significance, a comprehensive understanding of global research trends, key contributors, and emerging themes in ALI remains underexplored. Objective: This study aims to perform a bibliometric analysis of ALI-related research, identifying trends, influential contributors, and areas for future exploration. Methods: Data were retrieved from the Scopus database using relevant keywords. Bibliometric metrics were analyzed using VOSviewer and Biblioshiny, focusing on publication trends, co-authorship networks, and keyword co-occurrence. Descriptive and visual analyses highlighted the leading journals, nations, and emerging research themes in ALI. Result: A total of 1,967 documents were identified, with a surge in publications from 2020 to 2021, likely driven by the COVID-19 pandemic's thrombotic implications. The United States led global research efforts with 28.5% of corresponding author articles and the highest citation impact. Annals of Vascular Surgery and Journal of Vascular Surgery emerged as the most relevant and influential journals, respectively. Keyword mapping identified "acute limb ischemia," "peripheral arterial disease," and "vascular surgery" as central themes, with emerging topics including novel anticoagulants, mechanical circulatory support, and congenital risk factors like persistent sciatic artery and congenital heart disease. Despite advancements, gaps persist in systematic reviews, meta-analyses, and evidence-based clinical evaluations. Conclusion: This study provides a comprehensive overview of ALI research, identifying trends and highlighting opportunities for further investigation. By addressing existing gaps and integrating emerging guidelines—such as the 2024 ESC and ACC recommendations—future research can advance clinical practice and improve outcomes for patients with ALI.